Minimization of Overcapacity with Optimization of Policies to Tightening Prisons in Singaraja Class IIB Penitentiary Institutions - Ni Ketut Sari (Advances in Police Science Research Journal, 2021)
The purpose of this study to determine the policy of tightening the imposistion of crimes that can minimize overcapacity in Class IIB Singaraja prisons; to analyze the participation of the community and law enforcement officials in supporting the implementation of the correctional system in Singaraja Class IIB prison from a human rights perspective to realize the objectives of punishment. This type of research is normative research with statutory approach and conceptual approach. The source of primary legal materials used in this research is based on statutory regulations by emphasizing the search for norms contained in statutory provisions. The analysis technique used in this research is legal hermeneutic analysis technique which is described in a qualitative descriptive way. The results showed that the strict implementation of the policy of tightening the improsition of penalties in singaraja Class IIB prisons can overcome the negative impact of overcapacity. The implementation of the correctional system with a human right perspective minimizes the tightening of the imposition of imprisonment policies by increasing the participation of the community and law enforcement officials in supporting the realization of the objective of pubishment in the Class IIB Singaraja prison.